E-voice in the digitalised workplace. Insights from an alternative organisation - Vanessa Sandra Bernauer; Angela Kornau (Human Resource Management Journal, 2022)
Digitalisation permeates all aspects of organizational life, especially the ways we communicate with each other. Drawing on a case study of an alternative organisation - the German collective Premium, which is almost entirely digitally organised - we seek to explore contextual factors that facilitate or hinder the expression of electronic voice (e-voice). Based on 20 semi-structured interviews with different members of the collective, we identified various contextual facilitators and barriers to e-voice expression: Collective belief in the value of diverse voices, cautious online and complementary face-to-face communication facilitate e-voice, while less formalised structures, power and knowledge asymmetries, and information overload hinder it. These findings demonstrate that despite an alternative organisation's firm intention and self-reflective efforts to create an inclusive and participatory digital space, tensions arise. Further, our study contributes to employee voice theorising by outlining contextual factors that are specifically relevant to e-voice practices.
Keywords: 650; alternative organisation; collective; digitalisation; e-voice; electronic voice; employee voice